The potential of using organic acids in poultry farming to reduce microbial burden and increase productivity (Review) - Saleeva I.P.; Morozov V.Yu.; Kolesnikov R.O.; Ilyina L.A.; Sukhanova S.F.; Sokolova K.A.; Voropaev V.V. (BIO Web of Conferences)
Intensive poultry farming technologies make it possible to increase the production of eggs and meat every year, and this leads to problems with veterinary safety. To ensure the well-being of enterprises, the veterinary service must strictly observe the implementation of sanitary and hygienic measures. The increasing production of poultry products and the need to improve disinfection methods and means necessitate the search for new effective and safe means of disinfection of the air environment, equipment surfaces, hatching and food egg shells, poultry carcasses, drinking water, etc. An alternative to chemical disinfectants may be the use of organic acids to disinfect the air environment of poultry facilities in the presence of poultry, equipment surfaces, hatching and food egg shells, poultry carcasses, etc. Organic acids are found in plants mainly in the form of salts and esters, but they can also be obtained by microbiological synthesis. Organic acid-based disinfectants are considered to be toxicologically safe and biologically active. A promising direction is also the search for strains capable of biosynthesis of organic acids (such as butyric, propionic, lactic), which, on the one hand, can reduce the pathogenic load on the animal body by lowering the pH in the digestive tract, and on the other hand, serve as a source of nutrition. In a number of in vitro studies, evidence has been obtained that bacteriocins, which are antimicrobial peptides of bacterial origin, can become a promising alternative to traditional antibiotics in poultry farming. One of the interesting innovative solutions is the Micromet water bio-oxidizer (produced by BIOTROF, Russia), which is an excellent alternative to chemicals. The use of new preparations to reduce the microbial burden on the bird’s body is an urgent topic and has prospects for further work in this direction.